Analysis of Arabic, Nahwu, and Shorof Teachers’ Perspectives on the Study of Nahwu and Shorof at Madrasah Aliyah Al-Hidayah in East Tanjung Jabung - Zaldy Ahmad; Afriana Santosa (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study was motivated by the fact that students still experience difficulties in understanding Nahwu and Shorof despite studying both sciences in Islamic boarding schools. The purpose of this research was to examine the perspectives of Arabic language, Nahwu, and Shorof teachers regarding the importance of Nahwu and Shorof in Arabic language learning, their understanding of the concepts and applications, and the effectiveness of learning implementation at Madrasah Aliyah Al-Hidayah East Tanjung Jabung. This research employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that teachers considered Nahwu and Shorof as the fundamental basis of Arabic language learning because these sciences regulate sentence structures, word transformations, and meanings in Arabic texts. Teachers believed that mastery of Nahwu and Shorof is essential for understanding the Qur’an, hadith, and classical Islamic books. The learning process was considered fairly effective since many students already had prior knowledge from pesantren education and showed progress during the learning process. However, the effectiveness of learning still faced several obstacles, including low student motivation, differences in students’ basic abilities, limited learning time, and the complexity of the material. This study concludes that improving the quality of Nahwu and Shorof learning requires more varied teaching methods, continuous motivation, regular material reinforcement, and stronger institutional support.